Radio-Frequency Safety Assessment of Stents in Blood Vessels During Magnetic Resonance Imaging - Fujimoto, Kyoko; Angelone, Leonardo M.; Lucano, Elena; Rajan, Sunder S.; Iacono, Maria Ida (Frontiers in Physiology, 2018)
Purpose The purpose of this study was to investigate the need for high-resolution detailed anatomical modeling to correctly estimate radio-frequency (RF) safety during Magnetic Resonance Imaging (MRI). RF-induced heating due to metallic implanted devices depends on the electric field tangential on the device (Etan). Etan and Specific Absorption Rate (SAR) were analyzed in blood vessels of an anatomical model to understand if a standard gel phantom accurately represents the potential heating in tissues due to passive vascular implants such as stents. Methods A numerical model of an RF birdcage coil and an anatomically realistic virtual patient with a native spatial resolution of 1mm3 were used to simulate the in vivo electric field at 64 MHz (1.5 T MRI system). Maximum values of SAR inside the blood vessels were calculated and compared with peaks in a numerical model of the ASTM gel phantom to see if the results from the simplified and homogeneous gel phantom were proportional to the results from the anatomical model. Etan values were also calculated in selected stent trajectories inside blood vessels and compared with the ASTM result. Results Peak SAR values in blood vessels were up to ten times higher than those found in the ASTM standard gel phantom. Peaks were found in clinically significant anatomical locations, where stents are implanted as per intended use. Furthermore, Etan results showed that volume-averaged SAR values might not be sufficient to estimate RF safety. Conclusion Computational modeling with a high-resolution anatomical model indicated higher values of the incident electric field compared to the standard testing approach. Further investigation will help develop a robust safety testing method which reflects clinically realistic conditions.